Eclampsia: Experience in 30 years at the National Hospital Edgardo Rebagliati Martis - IPSS - Pacheco Romero, José (2015)
Thirty years experience with eclampsia at Hospital Nacional Edgardo Rebagliati Martis is reviewed. Incidence was 0,038%, unchanged in the past 25 years. In most cases, neither past history not obstetrical or blood pressure characteristics led to the suspicion of this seriuos complication. It is necessary to have a high index of suspicion in women with high blood pressure acceleratio, epigastric pain, visual alterations, headache and anxiety. Delivery has to be as soon as treatment for convultions has been started. Maternal mortality was 18,94% and perinatal mortality 17,7%, rates that should determine future attitudes at our institution to improve them.